2021
DOI: 10.30659/odj.8.1.6-17
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease : A Rise in Prevalence in Military Troops Penyakit Periodontal

Abstract: Background: Oral condition is one of substantial factors in general health. Good oral health will determine dental fitness or readiness in military troops. Oral diseases affecting soldiers may have negative impacts in readiness on deployment or fight and contributes to lowering morale among personnel. At the recruitment stage, the prevalence of periodontal disease is low and controlled before the commencement of the training. As a matter of fact, periodontal health was not considered to be maintained and found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The main cause of NUG is opportunistic fusospirochetal infection caused by symbiotic oral flora, especially predisposed to a weakened immune system. 16 A study showed that 78% of all microorganisms cultured in necrotic lesions of NUG patients were Gram anaerobic (-) bacteria. 17 Spirochetes and most gram-negative bacteria, including Bacteroides intermedius, and fusiform sp.…”
Section: Casementioning
confidence: 99%
“…The main cause of NUG is opportunistic fusospirochetal infection caused by symbiotic oral flora, especially predisposed to a weakened immune system. 16 A study showed that 78% of all microorganisms cultured in necrotic lesions of NUG patients were Gram anaerobic (-) bacteria. 17 Spirochetes and most gram-negative bacteria, including Bacteroides intermedius, and fusiform sp.…”
Section: Casementioning
confidence: 99%
“…In the human body, vitamin C is capable of being found in an unbound state within both the interstitial fluid and blood. This unique characteristic allows it to function as either an antioxidant or reducing agent, depending on the circumstances [25]. Vitamin C is easily oxidized when exposed to free radicals because it has two -OH groups linked by a double bond.…”
Section: Antioxidant Activity Of Endophytic Fungi Extract Of Mango Mi...mentioning
confidence: 99%
“…Some changes in the oral cavity can occur due to a relationship with behavior. 54 In this study, data collected from a questionnaire to obtain pilot flight hours, bruxism and stress levels. After that, the teeth that were subjected to attrition and abfraction were scored.…”
Section: Introductionmentioning
confidence: 99%